Papillary and Callous Scales in the Integument of Agamid Lizards (Agamidae, Sauria) as a Phenomenon of Extraordinary Development of the Corneous Layers - Tatjana N. Dujsebayeva; Natalia B. Ananjeva; Nasrullah Rastegar-Pouyani; Awadh M. Al-Johany; Daniel A. Melnikov (Animals)
Scaled integument of six species of the genus Acanthocercus and Laudakia nupta, family Agamidae was studied using light and scanning electron microscopy. Gross observation revealed the presence of two types of modified scales in the males. The enlarged scales covered with an extremely thick β-corneous layer were detected in the dorsal and ventral surfaces of the tail base and on the palmar and plantar limb surfaces of all species. After detachment of the β-layer, the surface of such scales was covered with high papillae (“papillary scales”). The callous scales were found in the precloacal region of Acanthocercus species and in both precloacal and mid-ventral regions of L. nupta. Modified scales were found in some females and subadut specimens, and absent in juveniles. A prominent papillary layer characterized the dermis of both scale types. It was assumed that well-developed dermal papillae in such scales expended the total surface area of stratum germinativum and created a pool of proliferated cells in the interpapillary loops to increase the production of differentiating keratinocytes. These processes were undoubtedly associated with the formation of a thick and resistant corneous layer that distinguished both types of scales. Functional role, a taxonomic value, and analogies with normal and pathological epidermis in birds and mammals are discussed.